Clarify the effect of reversed austenite on the pitting corrosion resistance of super 13Cr martensitic stainless steel. (1st April 2023) - Zhao, Yonggang; Zhu, Zhiyuan; Zhao, Xuhang; Tian, Ruichao; Lei, Yun; Yu, Pengfei; Peng, Haoping; Chen, Longjun
Abstract: The effect of reversed austenite on the pitting behavior of super 13Cr martensitic stainless steel (S13Cr MSS) was investigated. The results revealed that reversed austenite was a FCC structure with Ni enrichment after tempering process, and there were no Ni-depleted regions adjacent to it. The reversed austenite content increased with increasing tempering temperature, and the pit depth decreased, as well as the dispersion degree of the Kelvin potential distribution. The reversed austenite reduced the risk of pitting corrosion through increasing the passive film compactness, and inhibiting Cl - penetration. Accordingly, the pitting corrosion resistance was enhanced as the tempering temperature increased. Highlights: Ni enriched reversed austenite content increased as the tempering temperature increased. Reversed austenite formation restricted the movement of dislocations and reduced the dislocations density in the S13Cr MSS. Reversed austenite reduced pitting corrosion through increasing the passive film compactness and inhibiting Cl - penetration. High reversed austenite content led to the good pitting corrosion resistance for S13Cr MSS.